2006
DOI: 10.1634/stemcells.2005-0265
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Hematopoietic Stem Cells into Ischemic and Growing Kidneys Suggests a Role in Vasculogenesis but Not Tubulogenesis

Abstract: Transplantation of murine bone marrow-derived stem cells has been reported recently to promote regeneration of the injured kidney. We investigated the potential of human adult CD34؉ progenitor cells to undergo renal differentiation once xenotransplanted into ischemic and developing kidneys. Immunostaining with human-specific antibodies for tubular cells (broad-spectrum cytokeratin), endothelial cells (CD31, PECAM), stromal cells (vimentin), and hematopoietic cells (pan-leukocyte CD45) demonstrated that althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 48 publications
7
53
0
1
Order By: Relevance
“…We have recently suggested a role for human CD34 þ hematopoietic stem cells (enriched for the endothelial progenitor marker CD133) in vasculogenesis and not tubulogenesis, after their engraftment in ischemic murine kidneys. 28 Similar findings of peri-tubular vascularization were reported in postischemic kidneys 34 and more progressive renal injury. 42 Furthermore, in a different model system, Rookmaaker et al 27 induced murine experimental glomerulonephritis and showed that whole murine bone marrow-derived cells (not fractioned into stem cell subtypes) participates in endothelial repair in injured glomeruli.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We have recently suggested a role for human CD34 þ hematopoietic stem cells (enriched for the endothelial progenitor marker CD133) in vasculogenesis and not tubulogenesis, after their engraftment in ischemic murine kidneys. 28 Similar findings of peri-tubular vascularization were reported in postischemic kidneys 34 and more progressive renal injury. 42 Furthermore, in a different model system, Rookmaaker et al 27 induced murine experimental glomerulonephritis and showed that whole murine bone marrow-derived cells (not fractioned into stem cell subtypes) participates in endothelial repair in injured glomeruli.…”
Section: Discussionsupporting
confidence: 67%
“…Histopathology of adult kidneys 24-48 h after ischemia showing lumen obliteration with loss of brush border as well as the disappearance of nuclei and necrosis of tubular cells has been previously demonstrated. 28 We analyzed SCL transcript levels along with the VEGF receptors FLK1 and FLT1, which have been shown to participate in the angiogenesis of ischemic limb and heart 33 at consecutive time points after ischemic injury. Realtime PCR demonstrated an early decline followed by rapid upregulation of SCL mRNA, peaking 48 h after ischemia (Figure 2).…”
Section: Scl Flk1 and Flt1 Mrna Expression In Regenerating Kidneysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies demonstrated that intrarenal cells, not BMSCs, seem to be responsible for cellular the reconstituted regions of the transplanted kidneys. Our follow-up revealed a declining trend in Ki-67 exreconstitution of the nephron following ARF (4,14).…”
Section: Introductionmentioning
confidence: 66%
“…Recently, however, by deconvolution microscopic analysis, Duffi eld et al (2005) suggested that tubular epithelial regeneration by BMDC was likely artifacts caused by the staining technique or the superimposition of a tubular cell and an infi ltrating BMDC. Xenotransplantation of human hematopoietic stem cells into immunodefi cient mouse kidneys after I/R injury demonstrated that these cells did not readily acquire a renal tubular cell phenotype and were restricted to hematopoietic lineage and, to a limited extent, endothelial lineages (Dekel et al 2006). Thus, it remains to be clarifi ed whether the cell source of tubular repair is the proliferation of endogenous renal cells or/and BMDC (Krause and Cantley 2005).…”
Section: Discussionmentioning
confidence: 99%